Anti-GAD65 Containing Cerebrospinal Fluid Does not Alter GABAergic Transmission - Hackert, Jana K.; Müller, Lorenz; Rohde, Marco; Bien, Christian G.; Köhling, Rüdiger; Kirschstein, Timo (Frontiers in Cellular Neuroscience, 2016)
Glutamic acid decarboxylase of 65 kDa (GAD65) antibodies have been reported in a variety of neurological disorders such as stiff-person syndrome, sporadic ataxia and some cases of epilepsy. Since the target is believed to be the cytoplasmic enzyme GAD65, the key enzyme of gamma-aminobutyric acid (GABA) synthesis, the pathophysiological role of these antibodies is poorly understood. Here, we stereotactically injected human cerebrospinal fluid (CSF) containing GAD65-antibodies into the hippocampus of rats in vivo and then prepared hippocampal slices 1-2 days after post-operative recovery. We characterized both evoked and spontaneous GABAergic transmission in vitro using sharp microelectrode and patch-clamp recordings in CA1 neurons. Intracellular recordings with sharp microelectrodes from CA1 neurons showed that evoked GABAAR- or GABABR-mediated inhibitory postsynaptic potentials remained unaltered in anti-GAD65 tissue. These results were confirmed with patch-clamp recordings showing no difference in evoked gabazine-sensitive inhibitory postsynaptic currents. In addition, spontaneous IPSCs also showed no difference between anti-GAD65 tissue and controls with respect to the mean frequency, the mean amplitude and the sIPSC distribution. In conclusion, stereotactic injection of GAD65-antibodies into the hippocampus leaves evoked and spontaneous GABAergic synaptic transmission intact. Hence, dysfunction of the inhibitory GABAergic system does not appear to be the major mechanism of epileptogenicity in this disease.